Every session counts: the differential impact of previous programmes and current programme dosage on offender recidivism - Kroner, Daryl G. (Legal and criminological psychology, 2012)
Purpose. The present study examined the impact of current treatment dosage on recidivism among offenders. Methods. Using a sample of dropouts from a community treatment programme, current treatment dosage and past completed programmes were used to predict criminal recidivism. Results. After statistically controlling for risk levels, only current dosage was predictive of recidivism. Conclusions. Offenders’ current direction, indicated by current dosage, is central to reducing recidivism. Strategies for offenders completing treatment sessions are discussed.